2020
DOI: 10.1088/1748-9326/ab738f
|View full text |Cite
|
Sign up to set email alerts
|

Observational constraints on the effective climate sensitivity from the historical period

Abstract: The observed warming in the atmosphere and ocean can be used to estimate the climate sensitivity linked to present-day feedbacks, which is referred to as the effective climate sensitivity (S hist ). However, such an estimate is affected by uncertainty in the radiative forcing, particularly aerosols, over the historical period. Here, we make use of detection and attribution techniques to derive the surface air temperature and ocean warming that can be attributed directly to greenhouse gas increases. These serve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 40 publications
(49 reference statements)
5
22
1
Order By: Relevance
“…Many studies have combined reconstructions of surface temperature and ocean heat uptake with estimates of radiative forcing to calculate the effective climate feedback during the historic period (e.g. Annan, 2015;Anan and Hargreaves, 2020;Bodman and Jones, 2016;Lewis and Curry, 2014;Skeie et al, 2018;Otto et al, 2013;Tokarska et al, 2020). However, climate feedback strengths evolve over time in complex climate models (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have combined reconstructions of surface temperature and ocean heat uptake with estimates of radiative forcing to calculate the effective climate feedback during the historic period (e.g. Annan, 2015;Anan and Hargreaves, 2020;Bodman and Jones, 2016;Lewis and Curry, 2014;Skeie et al, 2018;Otto et al, 2013;Tokarska et al, 2020). However, climate feedback strengths evolve over time in complex climate models (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…(2), have either calculated a single constant climate sensitivity (see Annan, 2015;Anan and Hargreaves, 2020;Bodman and Jones, 2016;Lewis and Curry, 2014;Sherwood et al, 2020;Skeie et al, 2018;Otto et al, 2013), or have evaluated ECS for specific historic periods (e.g. Tokarska et al, 2020), acknowledging that the value for the specific historical period may not apply for all timescales into the future.…”
Section: Ecs( ) =mentioning
confidence: 99%
“…Upon our use of blended CMIP6 temperature output for these GCMs and calculation of AAWR for 1975-2014, we find that AAWR based on blended CMIP6 temperature is 3.5 % lower than AAWR found when using only TAS. Tokarska et al (2020b) estimate an effect of 0.013 • C per decade in the trend of CMIP6 temperature output upon the use of blended CMIP6 temperature instead of TAS, while Cowtan et al (2015) report a difference of 0.030 • C per decade between the trend in observations and modeled output. Since the difference between values of AAWR found using blended CMIP6 temperature output and TAS is so small and does not affect any of our conclusions, we use TAS output from the CMIP6 multi-model archive because this choice allows many more GCMs to be examined.…”
Section: Attributable Anthropogenic Warming Ratementioning
confidence: 96%
“…We address this question by first comparing the above results to an estimate based on the portion of the observed surface and ocean warming that has been attributed to increasing GHGs (Tokarska, Schurer, et al, 2020): ΔT ghg , ΔF ghg , and ΔN ghg . Attribution makes use of the time-space pattern of warming to disentangle the effects of other forcings, particularly aerosols, from those of GHGs and then applies the same energy budget (Equation 20) as above, but uses attributed warming and greenhouse-gas-only forcing changes.…”
Section: Consistency With Estimates Based On Other Forward Modelsmentioning
confidence: 99%
“…Illustration of probability density functions from alternative, published approaches (as labeled). Tokarska, Schurer, et al (2020) rely on an energy budget approach using the observed warming and ocean heat uptake attributed to greenhouse warming and is most directly comparable to our main approach. The solid line relies on a flat prior in S, the dashed line is directly sampled (see text; similar to green line in Figure 11), and the dotted line is the same as the solid line, but based on doubled variance of climate variability when deriving the attributed warming estimates.…”
Section: Consistency With Estimates Based On Other Forward Modelsmentioning
confidence: 99%